Attitudes and knowledge about obstructive sleep apnea among Latin American primary care physicians - Cherrez-Ojeda, Iván; Jeffe, Donna B.; Guerrero, Thomas; Mantilla, Ronnie; Santoro, Ilka; Gabino, Gustavo; Calderon, Juan C.; Caballero, Fernan; Mori, Jose; Cherrez, Annia (Sleep medicine, 2013)
Objectives - We aimed to evaluate Latin American primary care physicians’ knowledge and attitudes about obstructive sleep apnea (OSA) using a Spanish-language version of the OSA Knowledge and Attitudes (OSAKA) questionnaire and to evaluate its psychometric properties. - Methods - We used a cross-sectional survey of general practice physicians in Ecuador, Peru, and Venezuela who completed the Spanish-language version OSAKA questionnaire. - Results - Of 684 primary care physicians surveyed, 367 (65%) responded (mean age, 45years; range, 21-75years). Mean total knowledge (proportion of 18 items correctly answered) was 60% (range, 0-100%). Less than half of physicians correctly answered the questions about the association between OSA and hypertension. We found no significant differences in overall knowledge in gender or time since graduation (⩽5years vs >5years). Although 73.5% of the physicians felt confident in identifying patients at risk for OSA, only 35.4% felt confident in managing those patients and 22.1% felt confident in managing patients with continuous positive airway pressure (CPAP) therapy. The Spanish-language version of the OSAKA questionnaire had comparable psychometric properties to the English-language version. - Conclusions - This Spanish-language version of the OSAKA yielded considerable variance in Spanish-speaking physicians’ knowledge about OSA and confidence in identifying and managing patients with OSA. Focused OSA education for Latin American general physicians is needed.